Isoniazid And Rifampicin Induced Hepatoprotective Activity Of Root And Leaves Extract Of Picrorhiza Kurroa (Journal of Pharmaceutical Negative Results, 2022)
Picrorhiza kurroa is an important medicinal herb in traditional ayurvedic and Tibetan medicine. It has been used for centuries to treat a variety of diseases, including liver disease. Present studies have suggested that Picrorhiza kurroa have potential as a therapeutic agent for treating Isoniazid−rifampicin. Isoniazid-rifampicin is anti-tubercular that is commonly used in industrial and laboratory settings. Exposure to Isoniazid-rifampicin can cause damage to the liver, resulting in severe liver diseases. The protective effect of Picrorhiza kurroa root and leaves on INH and RFP-induced liver injury involve regulating multiple pathways. The results of the Picrorhiza kurroa root and leaves show the prevention and treatment of the Isoniazid−rifampicin -induced liver injury. In addition, antioxidant also plays a critical role in the treatment of Isoniazid−rifampicin -induced liver injury. However, Picrorhiza kurroa root and leaves have both antioxidant and pro-oxidative effects. High-dose of Picrorhiza kurroa root and leaves (200 mg/kg) may act as a pro-oxidant and cause oxidative stress as compared to lower dose with promising action. The protective effect of Picrorhiza kurroa root and leaves on Isoniazid−rifampicin -induced livery injury were presented in this work. Further research should be carried out to discover novel solutions for preventing and treating Isoniazid−rifampicin-induced liver injury and the detailed molecular mechanisms involved in Picrorhiza kurroa root and leaves protective effect.